The Effect of Tuber Size and the Addition of Organic Materials on the Growth and Yield of Garlic Plants (Allium sativum L.) Var. Lumbu Kuning - Rizkiyatul Awwalu Bil Khikmah; Makhziah Makhziah; Hadi Suhardjono (The University of Lampung, 2025)
Efforts to increase garlic productivity can be achieved through cultivation innovations, such as selecting the appropriate tuber size and incorporating organic matter. This study aimed to determine the optimal combination of tuber size and organic matter to increase garlic yield. The research was arranged using a Split Plot Design (SPD) within a Randomized Block Design, with three replications. The main plots involved organic matter treatments: (1) no organic matter, (2) biochar (1 kg/m²), (3) biochar + manure (0.5 kg/m²:0.5 kg/m²), and (4) manure (1 kg/m²). The subplots consisted of tuber size categories: (1) small tubers (0.3-0.6 g), (2) medium tubers (0.7-1 g), and (3) large tubers (1.1-1.4 g). Results showed an interaction between large tuber sizes and the addition of manure, which produced the highest fresh bulb weight. Additionally, the combination of large tuber sizes with the addition of biochar and manure resulted in a high dry bulb weight. Keywords: Biochar, Manure, Nutrient, Production.